2012
DOI: 10.4049/jimmunol.1101686
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Dendritic Cells from B6.NZM Sle1/Sle2/Sle3 Lupus-Prone Mice Express an IFN Signature That Precedes Disease Onset

Abstract: Patients with systemic lupus erythematosus (SLE) show an over-expression of Type I Interferon (IFN) responsive genes called “Interferon Signature”. We found that the B6.NZMSle1/Sle2/Sle3 (Sle1,2,3) lupus-prone mice also express an Interferon Signature compared to non autoimmune C57BL/6 mice. In vitro, myeloid dendritic cells (mDCs)(GM-CSF bone marrow-derived BMDCs) from Sle1,2,3 mice constitutively over-expressed IFN responsive genes such as IFNb, Oas-3, Mx-1, ISG-15 and CXCL10, and the members of IFN signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 88 publications
8
67
1
Order By: Relevance
“…Lupus patients have high levels of IFN α in their serum (31,32) and increased expression of IFN-responsive genes (29). The IFN signature has been reported in Sle1.Sle2.Sle3 mice (23). We found that IFN α levels were significantly increased in Sle1.Sle3 VISTA −/− mice compared with Sle1.Sle3 or B6 VISTA −/− mice (Figure 6A).…”
Section: Discussionmentioning
confidence: 85%
“…Lupus patients have high levels of IFN α in their serum (31,32) and increased expression of IFN-responsive genes (29). The IFN signature has been reported in Sle1.Sle2.Sle3 mice (23). We found that IFN α levels were significantly increased in Sle1.Sle3 VISTA −/− mice compared with Sle1.Sle3 or B6 VISTA −/− mice (Figure 6A).…”
Section: Discussionmentioning
confidence: 85%
“…To assess endogenous type I IFN activity, we measured expression of type I IFN signature genes in the spleens of NZM mice. We compared expression of type I IFN signature genes that were previously shown to be elevated in the lymphocytes of pre-disease lupus-prone mice compared to B6 mice (30). Using this previously validated assay, we found the absence of ERα significantly reduced the expression of the Type I IFN signature genes Cxcl-10 and Mx-1 in the NZM spleens (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…A Type I IFN Signature is up-regulated in PBMCs of SLE patients (Baechler et al, 2003; Bennett et al, 2003; Crow et al, 2003; Feng et al, 2006; Han et al, 2003) and in DCs from lupus prone mice (Sriram et al, 2012), and administration of exogenous Type I IFNs accelerates autoimmunity in lupus prone mice (Mathian et al, 2005). Therefore, the results that curli-DNA composites accelerate the onset of autoimmunity in lupus-prone mice can be partially explained by the strong induction of Type I IFNs in DCs as well as by the polyclonal activation of the adaptive immune system, as curli up-regulated activation markers in splenic T and B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The more frequent outcome of Salmonella infection in bacteremia and complications in soft tissues in SLE patients (Lim et al, 2001; Pablos et al, 1994; Tsao et al, 2002) and the recent identification of increased levels of circulating endotoxin in SLE patients (Shi et al, 2014), support this hypothesis. In addition, since inflammatory cytokines can decrease intestinal mucosal barrier function (Turner, 2009), the high levels of cytokines present in pre-disease stages of lupus (Connolly and Hakonarson, 2012; Sriram et al, 2012), might compromise mucosal barrier function and allow the biofilm material produced by microbiota at mucosal sites to access the immune system, act as danger signals and trigger lupus onset.…”
Section: Discussionmentioning
confidence: 99%